PROFESSIONAL INTERVENTIONS TO REDUCE AND POSSIBLY ELIMINATE SUBGINGIVAL BIOFILMS AND CALCULUS. SUBGINGIVAL INSTRUMENTATION. REVIEW. - Maria-Alexandra Martu; Liliana Pasarin; Ionut Luchian; George-Alexandru Maftei; Oana Ciurcanu; Ioana Martu; Irina Georgeta Sufaru; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2023)
The clinical guidelines for the treatment of patients with periodontitis stages I-III published from the European Federation of after the patient has been informed about his/her condition, the first step in the treatment process is directed toward motivation, targeting behavioral changes to achieve adequate self-performed oral hygiene practices and controlling local and systemic modifiable risk factors. Frequent re-evaluation of oral hygiene reinforcement outcomes is suggested, aiming to reinforce a patient's motivation and keep the patient up to date with any changes that might occur in the periodontal status, enabling the patient to actively participate in the progress of the treatment plan. Periodontology in 2020, suggest treatment being provided to patients with periodontitis by a pre-established stepwise approach. The second step is focused on professional interventions to reduce and possibly eliminate subgingival biofilms and calculus. Promotes periodontal wound healing via reduction of tissue inflammation and shifts in the host responses.